PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH MELALUI PENDEKATAN SCAFFOLDING TERHADAP HASIL BELAJAR SISWA SMA NEGERI 3 PRAYA - Pujilestari Pujilestari (Lembaga Penelitian dan Pendidikan Mandala, 2016)
The aims of this research to determine the effect of the use of problem-based learning model through scaffolding approach to the learning outcomes math grade XI student of SMAN 3 Praya on statistics (measures of central tendency of data) in the academic year 2015/2016. This type of research is experimental research. The population in this study were all students of grade XI SMA 3 Praya of 48 students. The samples used were students of grade XI IPA 1 which consist of 25 students as experimental class and grade XI IPA 2 amounting to 23 students as the control classes are taken by simple random sampling technique (simple). Data in this study were drawn by providing initial test and final test to students in grade samples. Data collection techniques using expert validator. Based on preliminary tests gained an average of 32 experimental class and control class of 37. The results of the final tests showed an average of 70 experimental class and control class at the end of grade 61. The test data samples were analyzed using t-test. T-test results obtained tcount > ttabel 2,248 and 2,014. Tcount obtained greater than ttable the error level of 5% and horsepower by 46, it can be concluded that there are significant use of problem-based learning model through scaffolding approach to the learning outcomes of students' mathematics XI SMAN 3 Praya academic year 2015/2016